A Comparative Analysis of the Co-operative, Islamic and Conventional Banks in Malaysia - Azmah, Othman; Fatimah, Kari; Rosita, Hamdan (Scientific & Academic Publishing, 2013)
This paper evaluates the nature and extent of productivity change of the co-operative, Islamic and conventional banks in Malaysia over the period of 2006-2010. Bank Kerjasama Rakyat Malaysia Berhad (Bank Rakyat) is a co-operative bank that has been the backbone of the Malaysian co-operative movement. Bank Rakyat had played a significant role by continuously supporting the co-operative sector in contributing to the country’s economy. This study utilized a non-parametric Data Envelopment Analysis (DEA) methodology and Malmquist productivity index (MPI) to estimate the individual bank efficiency and productivity changes within this period. The results from this analysis showed that 64.3 percent of banks studied had total factor productivity (TFP) progress. Out of this 44 percent are Islamic banks. The MPI index summary had shown that TFP had regressed in 2007 by 6.2 percent. TFP summary of annual mean for the 5 year period however, showed a progressed in TFP of 1.5 percent that was contributed by 2.7 percent increase in technical efficiency. Results had indicated that Bank Rakyat is among the top banks that have achieved TFP increased out of the fourteen banks studied. The second stage empirical results based on Tobit regression also suggested that bank’s assets, status and loan intensity are statistically significant in determining TFP. Environmental factors however, were found to be insignificant determinant.